Ground stone lithic technology of the Indian Peaks, Colorado, USA - Pelton, Spencer R., author; LaBelle, Jason M., advisor; Leisz, Stephen, committee member; Stohlgren, Thomas, committee member (Colorado State University. Libraries, 2013)
Ground stone tools are a long-noted aspect of pre-contact archaeological assemblages from the high elevations (2975-3666 meters asl) of the Colorado Front Range (CFR). The tools are present in small frequencies at around 40% of the sites thus far recorded, and are typically present as heavily fragmented grinding slab fragments procured many kilometers east and meters of relief lower than the study area and a combination of local and non-local handstones in a wide array of morphological configurations. Compared to their chipped stone counterparts, ground stone tools typically comprise a small percentage of archaeological assemblages, and have thus been reported in a largely cursory fashion. Though the ground stone assemblage from a single site is too small and perhaps too homogenous to inform large-scale questions, they take on increased interpretive potential when synthesized in aggregate and on a regional scale. Drawing from a distributional approach to archaeology and a technological approach to artifact analysis, the present study addresses the behavioral implications of ground stone tool presence in the high altitudes of the CFR by employing a three-tiered morphological, temporal, and spatial analysis. A technological analysis of ground stone tools (chapter 4) is centered upon answering two primary research questions catered towards understanding the function and technological organization of the high altitude ground stone toolkit. Firstly, the idea that handstones were technologically flexible in function is tested through comparison of the size of and diversity of modifications present on local and non-local handstones. It is determined that non-local handstones are significantly smaller in mass than local handstones, and were thereby chosen for inclusion into mobile toolkits on this basis. However, contrary to expectations of a flexible tool, non-local handstones contain less diversity of modifications than local handstones, suggesting that they were transported for some specialized purpose that local handstones could not fulfill. For netherstones, the idea that some were used as cooking stones is tested, given the assumption that thinner stones would function better for this task and would subsequently exhibit thermal alteration on a more frequent basis. This hypothesis is not proven, suggesting that thermal alteration of grinding slabs is not related to use as cooking stones, or that thickness is not related to grinding slabs' function as cooking stones. A temporal analysis (chapter 5) is conducted to test a prior model of high altitude land use that anticipates a greater diversity of ground stone tool forms will be present in assemblages of early Archaic age, during which residential use of the study area is proposed to have increased in response to climate change. It is determined that, though this period contains the greatest diversity of ground stone tool forms both in terms of handstone morphology and grinding slab thickness, that diversity is almost entirely a function of sample size. The implications of these results are discussed and several needs for future diachronic studies in the region are called for. Finally, a distributional analysis (chapter 6) of ground stone tool presence is undertaken in order to test current models of land use for the Colorado Front Range; the 'rotary' model expects a largely random distribution of ground stone tools and the 'up-down' model expects a largely patterned distribution. It is determined that there are significant differences in the presence of ground stone tools between major ecological zones, and that each zone is provisioned with different ground stone tools types in roughly the same manner. Further, this significant difference is directional, and patterned in terms of the diversity of edible plants located within each ecological zone. These results are interpreted to be most supportive of an 'up-down' model of prehistoric land use.
Keywords: distributional analysis; technological organization; high altitude; ground stone; ecology